DEVELOPMENT AND VALIDATION OF STUDENT'S FINANCIAL ATTITUDE INSTRUMENTS - ., Fitri; ., Sarnawiah; Otoluwa, Narto Irawan (2020)
Financial attitude is an important component in financial literacy. This study aims to develop and validate student financial attitude instruments. This study involved 50 participants and this was in accordance with the number of samples using the Rasch model analysis. Financial attitudes are measured from the dimensions of controlling monthly expenses, setting financial targets for the future, saving money (saving) every month, how to manage money, having and following a monthly spending plan, filling balances on e-money (eg ovo, go-pay, paytren). ), compare deals, stay within the available budget or budget and invest regularly. The results showed that the dimensions related to the attitude of investing regularly in the context of students need to be removed because it is not in accordance with the misfit order, namely the value is outside the range of values of MNSQ, OUT.ZSTD and Point Correlation Measurement.